(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Numerous studies have been conducted on competitive intelligence and its impact on business performance. Most of companies agreed that competitive intelligence is a critical element of business and corporate strategy to increase income hence investment in competitive intelligence considered to be profitable. This research is aimed to expand the knowledge boundary by investigating the application of Competitive Intelligence in electrical power plant company. Twenty companies were selected as the target sample using purposive sampling design, in which the questionnaires were distributed to 120 individuals who were argued to have knowledge in the practice of Competitive Intelligence. In total, 105 questionnaires were returned for further analysis. Data were analyzed using descriptive statistic provided by SPSS. In the aspect of Competitive Intelligence Practices, results indicated that the mean score for each individual item range between 3.23 to 4.14, suggesting intensive practices of Competitive Intelligence. In the aspect of Utilization of Tools in practicing Competitive Intelligence, results indicated that three most widely used tools were from Employees, Customers and Internet. In the aspect of measurement variables in measuring competitive intelligence practices, results indicated that three most widely used measures were (1) yearly improvement of Equivalent Availability Factor-EAF (mean 3.96), (2) increase in percentage of planned maintenance (mean 3.82), and (3) yearly improvement of Equivalent Forced Outage Rate – EFOR (mean 3.75). Public utilities (infrastructure) company usually being pictured as companies that does not really care about competition as they usually being run by the Government. However, the findings of this research show otherwise